Associated bacteria of Botryococcus braunii (Chlorophyta) - Joao D. Gouveia; Jie Lian; Georg Steinert; Hauke Smidt; Detmer Sipkema; Rene H. Wijffels; Maria J. Barbosa (PeerJ, 2019)
Botryococcus braunii (Chlorophyta) is a green microalga known for producing hydrocarbons and exopolysaccharides (EPS). Improving the biomass productivity of B. braunii and hence, the productivity of the hydrocarbons and of the EPS, will make B. braunii more attractive for industries. Microalgae usually cohabit with bacteria which leads to the formation of species-specific communities with environmental and biological advantages. Bacteria have been found and identified with a few B. braunii strains, but little is known about the bacterial community across the different strains. A better knowledge of the bacterial community of B. braunii will help to optimize the biomass productivity, hydrocarbons, and EPS accumulation. To better understand the bacterial community diversity of B. braunii, we screened 12 strains from culture collections. Using 16S rRNA gene analysis by MiSeq we described the bacterial diversity across 12 B. braunii strains and identified possible shared communities. We found three bacterial families common to all strains: Rhizobiaceae, Bradyrhizobiaceae, and Comamonadaceae. Additionally, the results also suggest that each strain has its own specific bacteria that may be the result of long-term isolated culture.